Congenital Heart Disease Increases Mortality in Neonates With Necrotizing Enterocolitis - Kessler, Ulf; Hau, Eva-Maria; Kordasz, Marcin; Haefeli, Stephanie; Tsai, Catherine; Klimek, Peter; Cholewa, Dietmar; Nelle, Mathias; Pavlovic, Mladen; Berger, Steffen (Frontiers in Pediatrics, 2018)
Background: Studies on the influence of congenital heart disease (CHD) on neonates with necrotizing enterocolitis (NEC) have produced varied results. We therefore examined the influence of CHD on NEC outcomes. Methods: We carried out a retrospective single-center study including infants with confirmed NEC, treated between 2004 and 2017. We excluded patients with isolated patent ductus arteriosus or pulmonary hypertension (n = 45) and compared outcomes of patients with hemodynamically relevant CHD (n = 38) and those without CHD (n = 91). Results: Patients with CHD were more mature than those without CHD [gestational age, median, 95% confidence interval (CI95), 37.1, 34.5–37.2w, vs. 32.6, 31.9–33.3w; P < 0.01]. The presence of CHD did not influence the frequencies of severe disease (overall 21% Bell stage III), nor surgical interventions (overall 30%), the occurrence of intestinal complications (overall 13%), nor the duration of hospitalization (overall 38 days in survivors). The overall mortality as well as NEC-related mortality was increased with the presence of CHD, being 50% (19 out of 38) and 13% (5 out of 38), respectively, when compared to patients without CHD, being 8% (7 out of 91) and 3% (3 out of 91). The presence of CHD and of advanced NEC stage III were independent predictors of NEC-associated fatalities with multivariable odds ratios (CI95) of 7.0, 1.3–39.5 for CHD, and of 3.4, 1.6–7.5 for stage III disease. Conclusions: While some outcome parameters in neonates with NEC remained unaffected by the presence of CHD, the mortality risk for patients with CHD was seven times higher than without CHD.